Best practices in dengue surveillance: a report from the Asia-Pacific and Americas Dengue Prevention Boards. - Mark E Beatty (Public Library of Science (PLoS), 2010)
Background Dengue fever is a virus infection that is spread by the Aedes aegypti mosquito and can cause severe disease especially in children. Dengue fever is a major problem in tropical and sub-tropical regions of the world. Methodology/principal findings We invited dengue experts from around the world to attend meetings to discuss dengue surveillance. We reviewed literature, heard detailed reports on surveillance programs, and shared expert opinions. Results Presentations by 22 countries were heard during the 2.5 day meetings. We describe the best methods of surveillance in general, the stakeholders in dengue surveillance, and the steps from mosquito bite to reporting of a dengue case to explore how best to carry out dengue surveillance. We also provide details and a comparison of the dengue surveillance programs by the presenting countries. Conclusions/significance The experts provided recommendations for achieving the best possible data from dengue surveillance accepting the realities of the real world (e.g., limited funding and staff). Their recommendations included: (1) Every dengue endemic country should make reporting of dengue cases to the government mandatory; (2) electronic reporting systems should be developed and used; (3) at minimum dengue surveillance data should include incidence, hospitalization rates, deaths by age group; (4) additional studies should be completed to check the sensitivity of the system; (5) laboratories should share expertise and data; (6) tests that identify dengue virus should be used in patients with fever for four days or less and antibody tests should be used after day 4 to diagnose dengue; and (7) early detection and prediction of dengue outbreaks should be goals for national surveillance systems.